Intimate Partner Violence Incidents and Solutions Reported by Turkish Couples in Long-Term Marriages: An Exploratory Qualitative Study - Mehmet A. Balkanlioglu; Zeynep Ozinci (Qualitative Sociology Review, 2022)
This qualitative study investigates the relationship between intimate partner violence (IPV) and the duration of marriage in the Turkish context and explores spouses’ perceptions, experiences, and solutions concerning IPV. Participants were thirty Turkish couples married for twenty or more years. Data collection tools were a semi-structured interview, observation notes taken during the interview, and a socio-demographic questionnaire. Data analysis showed that psychological violence was the most reported type, while sexual and economic violence was not reported in long-term marriages. Only a few instances of physical violence were reported during the first years of marriage. Regarding gender, the perpetrators of physical IPV were all men except for only one case, while both men and women were the perpetrators and victims of psychological violence. Spouses’ proposed solutions for IPV were identifying the determinants of IPV, encouraging religious and values education, solving economic problems, building communication and patience, learning respect, responsibility, and love; or getting divorced. The study suggests some implications for professionals.